Health economics of virtual versus face-to-face glaucoma clinics: a time-driven activity-based costing study - Rhiannon Tudor Edwards; Vishal Shah; Timothy L Jackson; Obeda Kailani; Joel Attlee (BMJ Open Ophthalmology)
Background/Aims Staffing represents the most significant cost to the National Health Service, and ophthalmology is its largest outpatient specialty. Value-based healthcare (VBH) focuses on care processes. Innovative models include a shift towards ‘virtual’ glaucoma services. We used VBH costing methodology to quantify personnel costs of virtual and face-to-face (F2F) glaucoma clinics.Methods Virtual and F2F clinics were process-mapped to produce step-by-step pathways of patients in each setting. Real-world timings were then audited, and time-driven activity-based costing was used to calculate the personnel cost-per-patient for both settings.Results Data were captured from 24 consecutive virtual glaucoma patients and 42 consecutive patients across two F2F clinics. The capacity cost rates in £/min were £0.24 for technicians and £1.16 for consultants. The average time taken to acquire clinical data in the virtual pathway was 39 min per patient (95% CI 36 to 43, range 27–61) with 14 min (95% CI 13 to 14, range 12–20) for their remote consultant review. The estimated personnel costs associated with a single virtual glaucoma clinic visit totalled £25.60 (95% CI £23.72 to £33.52). The average time taken to be seen in the F2F clinic was 50 min (95% CI 42 to 59 min, range 12–123 min) with a personnel cost of £31.08 (95% CI £19.70-£42.43).Conclusion Staff costs associated with visits to the consultant-delivered virtual and F2F glaucoma clinics were similar (p value=0.14), supporting virtual clinics to provide service capacity. The main limitations were that our study involved a single site, small sample size and did not consider the severity of glaucoma.